THE GRAMMATICAL COHESIVE DEVICES ERROR USAGE BY ENGLISH DEPARTMENT STUDENTS IN PUTERA BATAM UNIVERSITY - Robby Satria, Nurma Dhona Handayani (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This research is actually the continuation research of cohesive analysis whichalready presented before as the outing target of PDP funded by RistekDikti. If previouslythe analysis is about the frequency of grammatical cohesive, the further analysis is aboutgrammatical error of cohesive usage done by a students. The method for this research isquantitative descriptive which describes the real situation without examine hypothesis.This research analyzes the frequency of grammatical cohesive devices usage by thestudents of PuteraBatam University. The students as the object of the research are given atestin giving a description about social media. Basically students use grammaticalcohesive devices and it is found that from four types of devices, the most prominent devicesis references,followed by conjunction, Ellipsis and Substitution. After getting those result,the further analysis concern on grammatical cohesive devices error usage done by studentswiththe result mostly students have problem in theoverused of conjunction “and” and“because” and also the misuse of pronoun “it” and possessive determiner “its”, “ours”,“yours”, “theirs”.